Mamlakat LINGUISTIC ANALYSIS OF PUN AND WORDPLAY IN THE ENGLISH LANGUAGE: LINGUISTIC ANALYSIS OF PUN AND WORDPLAY IN THE ENGLISH LANGUAGE - Tojiboyeva, Mamlakat (Журнал иностранных языков и лингвистики, 2022)
This article considers the issues of linguistic analysis of word play in English. The authors of the article believe that the widespread use of a pun (play on words) in the English language, the agnostic attitude of many researchers to this linguistic phenomenon, which they enrolled in the list of “untranslatable” phenomena, dictates the need for a more complete study of the play on words: the study of the informative structure of the pun in close connection with its contextual characteristics and establishing the most adequate correspondences and possible options for transferring this technique to other languages. The paper opens with a corrective examination of the pun, the term ‘’pun’’ being frequently used too broadly by English-speakers to designate any and all form of word-play.